2022
DOI: 10.1093/femsre/fuac008
|View full text |Cite
|
Sign up to set email alerts
|

The microbial ecology ofEscherichia coliin the vertebrate gut

Abstract: Escherichia coli has a rich history as biology's ‘rock star’, driving advances across many fields. In the wild, E. coli resides innocuously in the gut of humans and animals but is also a versatile pathogen commonly associated with intestinal and extraintestinal infections and antimicrobial resistance—including large foodborne outbreaks such as the one that swept across Europe in 2011, killing fifty-four individuals and causing approximately 4 000 infections and 900 cases of haemolytic uraemic syndrome. Given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 315 publications
(316 reference statements)
0
19
0
Order By: Relevance
“…This study examined the role of oxygen in de novo acquisition of resistance by comparing resistance development under aerobic and anaerobic conditions. In the human intestines, E. coli is exposed to anaerobic or micro-aerobic conditions [34]. Anaerobic growth may therefore be more natural than the aerobic conditions used in most experiments involving E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the role of oxygen in de novo acquisition of resistance by comparing resistance development under aerobic and anaerobic conditions. In the human intestines, E. coli is exposed to anaerobic or micro-aerobic conditions [34]. Anaerobic growth may therefore be more natural than the aerobic conditions used in most experiments involving E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is a gram-negative genus, nonsporulating, facultative anaerobic bacterium that is mainly distributed in the gut of vertebrates. [14] Some E. coli can produce glycosidases involved in the transformation of exogenous substances, thereby producing their beneficial effects. For example, Han DH et al [15] have found that E. coli can produce β-glucuronidase to hydrolyze the glycosidic bond in baicalin, so as to produce baicalein.…”
Section: Gut Microbial Floramentioning
confidence: 99%
“…0.0347 20 = 2.00). Next, in the human gut, which is the habitat of E. coli , this bacterium is typically present in 10 6 colony forming units per gram of stool (Foster-Nyarko and Pallen 2022). A typical value for the amount of faeces in a human is one lb or 450 grams (Alexa Answers, Amazon, retrieved July 21, 2022).…”
Section: Terminologymentioning
confidence: 99%